Development of a GeoGebra-Assisted Transformation Geometry Textbook - Wantika, Restu Ria; Sulistyaningtyas, Annisa Dwi (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
The transformation geometry course is a mandatory course that studies the basic concepts of transformation geometry, including translation, reflection, rotation, dilation, and transformation composition. Transformation geometry courses cannot be separated from the activity of deductively deriving concepts, theorems and algorithms, so more skills are needed so that students can understand this course easily. Therefore, the transformation geometry course requires good and effective teaching materials which can encourage students to actively interact with each other and be able to understand the material effectively, namely in the form of textbooks. The method stages carried out in this research are needs analysis, preparation of textbooks, expert validation, revision of textbooks, trials and giving questionnaires and evaluation. The results of the student response questionnaire revealed that 80% of students stated that they strongly agreed with the use of this Transformational Geometry textbook and the results of student understanding were good, so the textbook developed was valid, practical and effective.